2017
DOI: 10.1093/neuros/nyx148
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Algorithm for Optimizing Care of Elderly Patients With Glioblastoma

Abstract: Further optimization of the medical and surgical care of elderly glioblastoma patients may be achieved by providing more beneficial therapies while avoiding unnecessary resection in those not likely to receive benefit from this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…A total of 76 studies were retrieved for full-text evaluation, and 57 were further excluded due to the following reasons: no appropriate control (n = 29), inclusion of younger patients (n = 20), and no sufficient data (n = 8). Therefore, 19 studies met our inclusion criteria and were selected for final meta-analysis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). There were no additional eligible studies from the manual search of the reference lists of these studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…A total of 76 studies were retrieved for full-text evaluation, and 57 were further excluded due to the following reasons: no appropriate control (n = 29), inclusion of younger patients (n = 20), and no sufficient data (n = 8). Therefore, 19 studies met our inclusion criteria and were selected for final meta-analysis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). There were no additional eligible studies from the manual search of the reference lists of these studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…Recent studies have shown that, in addition to conventional prognostic factors, the molecular profile of tumors can be used to select from these treatment alternatives. [3][4][5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Microsurgery's place within this framework remains unclear. 6,[18][19][20][21][22] Even though gross total resection (GTR) has been proven to increase OS, little data are available concerning the risks and benefits of resections in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…10,15,19,26 In the same multivariate model, treatment with both TMZ and XRT (HR 0.60 [95% CI 0.45–0.81, p = 0.001) and postoperative clinical trial enrollment (HR 0.54 [95% CI 0.41–0.71, p < 0.0001) were independent predictors of improved overall survival in our patient cohort.…”
Section: Resultsmentioning
confidence: 65%